2015
DOI: 10.1155/2015/532984
|View full text |Cite|
|
Sign up to set email alerts
|

Small Molecule Kaempferol Promotes Insulin Sensitivity and Preserved Pancreaticβ-Cell Mass in Middle-Aged Obese Diabetic Mice

Abstract: Insulin resistance and a progressive decline in functional β-cell mass are hallmarks of developing type 2 diabetes (T2D). Thus, searching for natural, low-cost compounds to target these two defects could be a promising strategy to prevent the pathogenesis of T2D. Here, we show that dietary intake of flavonol kaempferol (0.05% in the diet) significantly ameliorated hyperglycemia, hyperinsulinemia, and circulating lipid profile, which were associated with the improved peripheral insulin sensitivity in middle-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 57 publications
5
80
0
Order By: Relevance
“…Comparison of the 1 H and 13 C NMR data for fractions A and B revealed that these compounds are quercetin and kaempferol, respectively (Figure ) (Ibrahim, Amin, Ibrahim, Abdelzaher, & Abdelrahman, ). Interestingly, previous studies have demonstrated the antidiabetic activity of quercetin (Abdelkarem & Fadda, ; Srinivasan, Vijayakumar, Kothandaraman, & Palani, ; Yang & Kang, ) and kaempferol (Alkhalidy et al, ; Chandramohan, Al‐Numair, Alsaif, & Veeramani, ; Zang, Zhang, Igarashi, & Yu, ) in different models. The reduction in blood glucose shows that these compounds contribute to the blood glucose lowering activity of methanolic leaf extract of B. pinnatum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the 1 H and 13 C NMR data for fractions A and B revealed that these compounds are quercetin and kaempferol, respectively (Figure ) (Ibrahim, Amin, Ibrahim, Abdelzaher, & Abdelrahman, ). Interestingly, previous studies have demonstrated the antidiabetic activity of quercetin (Abdelkarem & Fadda, ; Srinivasan, Vijayakumar, Kothandaraman, & Palani, ; Yang & Kang, ) and kaempferol (Alkhalidy et al, ; Chandramohan, Al‐Numair, Alsaif, & Veeramani, ; Zang, Zhang, Igarashi, & Yu, ) in different models. The reduction in blood glucose shows that these compounds contribute to the blood glucose lowering activity of methanolic leaf extract of B. pinnatum .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the prevalence and sophistication of treatment, a 2.5%–15% annual health budget costs have been directly linked to the menace caused by diabetes (American Diabetes Association, ). Although the aetiology of this disease is not well characterized, there are indications of associated pancreatic β‐cells dysfunction (Alkhalidy et al, ). In addition to the elevated blood glucose, complications such as chronic inflammation, oxidative stress, lipotoxicity, endoplasmic reticulum (ER) stress (Ozcan et al, ; Poitout & Robertson, ) retinopathy (Hove, Kristensen, Lauritzen, & Bek, ), neuropathy (Moran et al, ), nephropathy (Huang et al, ), cardiovascular complications (Saely, Aczel, Marte, Langer, & Drexel, ) and ulcerations (Wallace et al, ) are well documented in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The STZ treatment results in insufficient production of insulin and thereby leads to elevated blood glucose levels (Giribabu, Kumar, Rekha, Muniandy, & Salleh, ). A previous study demonstrated that KF could decrease the blood glucose levels due to improved peripheral insulin sensitivity (Alkhalidy et al, ). Recently, it was also demonstrated that KF controls the blood glucose levels via promoting glucose metabolism in skeletal muscle and inhibiting gluconeogenesis in the liver (Alkhalidy et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…The STZ treatment results in insufficient production of insulin and thereby leads to elevated blood glucose levels (Giribabu, Kumar, Rekha, Muniandy, & Salleh, 2014). A previous study demonstrated that KF could decrease the blood glucose levels due to improved peripheral insulin sensitivity (Alkhalidy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…19,20) Intake of kaempferol ameliorates hyperglycemia, hyperinsulinemia and circulating lipid profile, which are associated with improved peripheral insulin sensitivity in mice fed a high-fat diet. 21,22) Upregulation of carnitine palmitoyltransferase 1 by p-coumaric acid improves liver fat metabolism. 23) Further studies are needed to clarify what components are effective for weight control.…”
Section: )mentioning
confidence: 99%